2015
DOI: 10.1007/s13762-015-0824-z
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodynamic behaviour and its effects on the treatment performance of panelled anaerobic baffle-cum filter reactor

Abstract: The aim of this paper was to present the influence of hydraulic behaviour in the treatment of sewage (domestic wastewater) using panelled anaerobic baffle-cum filter reactor (PABFR). The PABFR has five compartments of equal size in which the first three compartments operate as anaerobic baffled reactor (ABR) followed by anaerobic filters (AF). The combined reactor has a great potential for its application due to its panelled structure and arrangement of baffles inside each compartment. Hydrodynamic behaviour o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…A similar trend of COD removal using Kaldnes K3 media was also observed by Jaafari, et al [ 19 ] where a total removal of 95.5% was observed in a modified phoredox reactor for municipal wastewater treatment at an HRT of 8 h. Shebl, Hassan, Salama, El-Aziz, and Abd Elwahed [ 4 ] also observed similar trends of COD removal (75%) in their study for treating medium-high-strength wastewater at an HRT of 24 h in ABR. Furthermore, another study on an ABR-AF system by Renuka, et al [ 20 ] reported COD removal of 90% at an HRT of 40 h.…”
Section: Resultsmentioning
confidence: 99%
“…A similar trend of COD removal using Kaldnes K3 media was also observed by Jaafari, et al [ 19 ] where a total removal of 95.5% was observed in a modified phoredox reactor for municipal wastewater treatment at an HRT of 8 h. Shebl, Hassan, Salama, El-Aziz, and Abd Elwahed [ 4 ] also observed similar trends of COD removal (75%) in their study for treating medium-high-strength wastewater at an HRT of 24 h in ABR. Furthermore, another study on an ABR-AF system by Renuka, et al [ 20 ] reported COD removal of 90% at an HRT of 40 h.…”
Section: Resultsmentioning
confidence: 99%
“…The COD mass balance equation used for the present study considers the COD of the influent CODinf, effluent CODeff, biogas, aqueous biogas and the remaining portion as unaccounted COD (Renuka et al, 2015). Equation () gives the COD mass balance equation.…”
Section: Resultsmentioning
confidence: 99%
“…The combination of these processes enables the construction of models that are more compact, with lower power consumption by aerators due to the reduced dissolved oxygen demand and lower production of biomass (sludge). However, in order to ensure greater performance wastewater treatment, knowledge on the hydrodynamic characteristics of these reactors is of fundamental importance (Renuka et al, 2016). The hydrodynamics and the degree of mixing that occur in a biological reactor can strongly influence the degree of contact between the substrate and the bacteria, thus controlling mass transfer, the biological kinetics and the performance potential of the reactors (Liu et al, 2007;Tian;Chen, 2010;Mansouri et al, 2012).…”
Section: Introductionmentioning
confidence: 99%